(untitled) (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2026)
Giv’at Amal was founded during the 1948 war, when the houses in the Bedouin village of Al-Jammasin al-Gharbi, which borders Tel Aviv from the north-east, were inhabited by Jewish refugees from southern Tel Aviv. Tel Aviv City Hall, with the support of the government and the Histadrut, sought to evacuate village residents, tear down its buildings, and allocate its land toward the construction of neighborhoods for those nearest and dearest to it. Since then and until recently there was a fight between the residents, who clung to their homes, and the members of the establishment and private entrepreneurs that sought to evacuate them. The erasure of Jammasin, which became Jewish neighborhood Giv’at Amal, was mainly discussed from a critical viewpoint and presented as the victory of a heartless institution and greedy entrepreneurs over Mizrahi Jews of limited means, who had what little they did have taken from them by law. Thus far, scholars have focused on the Mizrahi ethnic identity of these residents as the central reason for the discrimination against them and their reduction to the status of a disadvantaged population within urban periphery. In this article, we take a geographic-historic approach that examines the transformation that took place within Giv’at Amal using historic resources: contemporary archives and newspapers, from the very first time Jews took residence in the area in 1948 to the completion of the evacuation of its homes in 2021, in order to obtain as thorough and comprehensive an understanding as possible of the Giv’at Amal Incident without relying on theories that redirect the study and its conclusions.